Bis(4-pyridyl) disulfide–2,2′-[(p-phenylenebis(oxy)]diacetic acid (1/1) - Wang, Guang-Yin (International Union of Crystallography, 2011)
The asymmetric unit of the title 1:1 co-crystal, C(10)H(8)N(2)S(2)·C(10)H(10)O(6), comprises two half-molecules, the bis(4-pyridyl) disulfide having twofold rotational symmetry and the 2,2′-[(p-phenylenebis(oxy)]diacetic acid having crystallographic inversion symmetry. In the disulfide molecule, the dihedral angle between the two pyridine rings is 86.8 (1)°, while the carboxyl groups of the substituted quinone lie essentially in the plane of the benzene ring [dihedral angle = 5.3 (1)°]. In the crystal, the components are linked via intermolecular O—H⋯N hydrogen bonds into zigzag chains which extend along c and are interlinked through C—H⋯π associations.